University Campus Bullying on Digital Platforms in Bangladesh: A Multimodal Discourse Analysis - Abdullah Al Mahmud; Syeda Kamrunnahar Eti (Asiatic: IIUM Journal of English Language and Literature, 2026)
This paper investigates how university-based digital platforms in Bangladesh have transformed bullying into complex and insidious forms. Using a multimodal discourse analysis framework, the study examines the linguistic and non-linguistic markers that bullies employ on these platforms. It collected qualitative data on digital bullying through 43 interviews with victims and from their social media conversations to identify specific patterns of language and digital discourses. The findings reveal that the rising types of bullying comprise identity-based practices, interactional aggression, and technologically mediated manipulation. Additionally, bullies strategically use language such as sarcasm, humour, insults, and backhanded compliments with multi-modal features (memes, GIFs, emojis, and captions) to disguise hostility. The study provides useful examples with critical reflections and insights for university digital platform administrators, cybercrime investigators, and policymakers at institutional and governmental levels.